On the performance of array antennas with mechanical distortion errors considering element numbers. Issue 3 (4th March 2017) - Wang, Congsi; Kang, Mingkui; Wang, Wei; Duan, Baoyan; Lin, Liwei; Ping, Lihao
ABSTRACT: Mechanical distortion errors in active phased-array antennas (APAA) include both random error and mechanical distortion. Random error is generated during the manufacturing and assembly process, and mechanical distortion is caused by external loads such as high thermal difference, vibration and impact loads. The combination of random error and mechanical distortion results in unexpected and significant degradation of the antenna electromagnetic performance, which has become an obstacle to development of high-performance APAA. After introducing the mechanical distortion errors into the antenna electric field as an additional phase factor, a coupled structural-electromagnetic model of the planar rectangular APAA was developed to describe the coupling relationship between mechanical distortion error and electromagnetic performance. The combined influences of the radiated element numbers, mechanical distortion and element position random error on the antenna electromagnetic performances are analysed, and valuable results for engineering application are discussed.